AUTOMATION OF THE SMART HOUSE SYSTEM-LEVEL DESIGN - Teslyuk, Vasyl; Beregovskyi, Vasyl; Pukach, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
In the article the smart house (SH) structural scheme, the general performance algorithm of the SH system, and the SH system model based on colored Petri nets, which enables exploring dynamics of the whole system as well as internal interaction of its main structural and functional subsystems at the system level design, have been developed.